Analysis of the Impact of Giving Rewards and Punishment to Increase Student’s Interest in Learning Indonesian in Class III of Taman Siswa Elementary School, Pematang Siantar - Veronika Nainggolan; Jubelando O. Tambunan; Chintani Sihombing (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the use of rewards and punishments in improving the learning outcomes of third-grade students at Taman Siswa Pematang Siantar Elementary School. A qualitative descriptive approach was used with a total of 23 students as research subjects. The data collection techniques used were observation, questionnaires, and documentation with data reduction analysis, data presentation, and conclusion/verification. Based on the results of the study, it was found that there was a lack of motivation and interest in learning as well as a passive attitude among students during learning activities. This was because teachers did not apply the right strategies. One strategy that can be applied is the use of rewards and punishments. The results showed that the implementation of rewards and punishments by teachers had a positive impact on increasing students' interest in learning. The impact of rewards based on the analysis of the reward questionnaire, per item with the highest score was on p4 (material rewards) at 94.57%. The average reward score percentage was 84.23% (good). The lowest score was on p5 (symbolic rewards) at 73.91% (fair). The impact of punishment based on the questionnaire analysis results with the highest score was p4 (non-verbal punishment) at 91.30% (very good). The lowest scores were on p6 (normative punishment) and p8 (psychological punishment) at 81.52% (good). The average percentage of punishment scores was 84.13% (good). This shows that the impact of punishment on learning interest was at a good level (85.65%). Students showed a positive response to both strategies and became more active in attending lessons.